Interdisciplinary perspectives on special and inclusive education in a volatile, uncertain, complex & ambiguous (VUCA) world - Narot, Pennee; Kiettikunwong, Narong (International perspectives on inclusive education ;, 2023)
Policy documents from the Organisation for Economic Co-operation and Development (OECD) and UNESCO have stressed the need to prepare students for what has been termed a VUCA (Volatile, Uncertain, Complex, and Ambiguous) world. The COVID-19 pandemic is an extreme case of a VUCA event that grants the opportunity to examine whether special and inclusive education is fully prepared for these complex situations. Interdisciplinary Perspectives on Special and Inclusive Education in a Volatile, Uncertain, Complex and Ambiguous (VUCA) World provides insights and examples from scholars in different disciplines across different regions, contexts, and systems. These ideas will help to shape how special students, teachers, and all the managerial components as a whole, will need to adapt to sustain and maintain inclusion in education in the circumstances of a VUCA world.